A high-barrier and high-fragrance coating composite film and its preparation process

By using NY film or BOPP film as the base material layer in the high-barrier coating film, polyvinyl alcohol composite film as the barrier layer, aqueous polyurethane ink as the ink layer, and PE composite film as the heat sealing layer. Combined with corona treatment and casting technology, the shortcomings in the barrier performance, fragrance retention and cost in the prior art are solved, and efficient and economical packaging material preparation is achieved.

CN119116503BActive Publication Date: 2025-03-28JIANGSU LEATER GREEN PACKAGING CORP LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411178318.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-27
Publication Date
2025-03-28
Estimated Expiration
2044-08-27

AI Technical Summary

Technical Problem

The existing high-barrier coating films have shortcomings in barrier properties, fragrance retention and cost, and are complex in processing, which increases the overall cost of packaging materials.

Method used

The structure design from the surface and the inner side is adopted, including NY film or BOPP film as the base layer, polyvinyl alcohol composite film as the barrier layer, aqueous polyurethane ink as the ink layer, and PE composite film as the heat sealing layer, which is prepared by corona treatment and casting processes to achieve close bonding and efficient barrier of the film layer.

Benefits of technology

It achieves high oxygen and water vapor barrier properties, excellent fragrance retention and mechanical strength, reduces costs, extends the service life of the product, and simplifies the processing technology.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119116503B_ABST
    Figure CN119116503B_ABST
Patent Text Reader

Abstract

The present invention discloses a high-barrier and high-fragrance coating composite film and a preparation process thereof, and belongs to the technical field of packaging materials. The high-barrier and high-fragrance coating composite film of the present invention comprises a substrate layer, a barrier layer, an ink layer and a heat-sealing layer, wherein the substrate layer is a NY film or a BOPP film, the barrier layer is a polyvinyl alcohol composite film, and the heat-sealing layer is a PE composite film; the polyvinyl alcohol composite film is composed of the following raw materials in parts by weight: 40-60 parts of polyvinyl alcohol, 10-15 parts of FDCA modified polyurethane compound, 8-15 parts of plasticizer, 2-4 parts of heat stabilizer, 0.1-0.3 parts of defoamer and 70-90 parts of deionized water. The coating composite film preparation process of the present invention is easy to operate, low in cost, has high oxygen barrier properties, water vapor barrier properties and fragrance retention properties, and has excellent mechanical strength, toughness and elasticity, and is not easy to break or perforate; the thickness of the isolation layer is lower than the conventional one, at about 0.5 μm, and still has high oxygen barrier properties and fragrance retention properties, which reduces the cost and ensures the use quality and life of the product.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of packaging materials, and in particular relates to a high-barrier and high-fragrance-preserving coated composite film and a preparation process thereof. Background Art

[0002] High barrier packaging film refers to materials with high barrier properties to oxygen, water vapor, carbon dioxide and aroma, and is mainly used in food, cigarettes, medicine, chemical packaging and other fields that need to preserve freshness and fragrance. With the increase of packaging functions in the market and the improvement of environmental awareness, high barrier packaging film has developed from single-layer film to multi-variety and multi-functional composite packaging film, and transparent barrier food packaging film on the market is usually realized by coating film.

[0003] Existing high barrier coating films are divided into substrate layer, printing layer, barrier layer and heat sealing layer according to their functions. Conventional substrate layers are made of materials such as BOPP (bi-stranded polypropylene), PET (polyethylene terephthalate), PE (polyethylene), PA (polyamide), NY (nylon), etc., which can ensure that the coating film has excellent mechanical strength and toughness, but the barrier performance to small molecules such as oxygen and water vapor is insufficient, which limits its single-layer use effect. Commonly used heat sealing layer materials are polyethylene, EVA, polypropylene and hot melt adhesives, among which polyethylene has good heat sealing, moisture resistance and cold resistance, but it is easy to scratch and perforate, has average gas barrier, is not resistant to high temperature, has poor ink adhesion and poor printing performance; cast polypropylene has good heat sealing, moisture resistance, average gas barrier, good printability, and is not cold-resistant; EVA has good heat sealing and good printability, but it has poor water barrier, is easy to hydrolyze, and has poor aging resistance, which in turn affects the use effect and service life of the packaging.

[0004] The barrier layer is a coating with special functions applied on the surface of the substrate layer. The barrier layer obtained by coating can give the film some new functions that the substrate layer does not have or has relatively poor functions, such as barrier properties, aroma retention properties, heat sealing properties and better printing properties. At the same time, it can meet the requirements of pasteurization resistance and cooking resistance on the packaging.

[0005] Existing barrier layers generally use aluminized film, aluminum-plastic composite film, PVDC film, EVOH film and PVA film. Aluminized film is a dense and uniform filter membrane formed on the surface of the base film by vacuum aluminum plating process. It has excellent barrier properties, but the equipment investment is large, the process requirements are high, the film layer is opaque, the folding resistance is poor, and it is difficult to recycle; aluminum-plastic composite film is composed of aluminum foil and plastic, and has good oxygen and moisture barrier properties, but the film layer is opaque, cannot be microwaved, and is difficult to recycle; PVDC film has excellent oxygen barrier and fragrance retention, excellent water resistance, transparency, and strong comprehensive food packaging performance, but when the waste packaging material is incinerated, dioxin carcinogens will be produced; EVO H film is easy to process, transparent, and has good barrier properties. It only produces CO2 and H2O when incinerated, and is an environmentally friendly material. However, if the barrier properties are to be achieved, the EVOH film layer is relatively thick, and there are certain requirements for processing equipment. The equipment investment cost is high, and the barrier properties decrease under high humidity conditions, affecting the use effect and life of the packaging material. The molecular structure of the PVA film is highly dense, and its barrier properties are better than PVDC. It is safe and environmentally friendly, but the PVA molecule contains a large number of hydroxyl groups, and the PVA coating has strong water absorption in the environment, which limits its application.

[0006] Invention patent CN202111204782.7 discloses a homogenous olefin packaging self-supporting bag, which has an MDOPE printing substrate layer, a PVA barrier layer, an aqueous ink layer, an adhesive layer and an LDPE heat-sealing layer from the outside to the inside. It has certain barrier properties and is green and environmentally friendly. However, the printing performance of the heat-sealing layer of the packaging self-supporting bag is not good, and it is necessary to use an aqueous polyurethane adhesive to ensure the bonding effect between the ink layer and the heat-sealing layer; each layer of the film is relatively thick, which increases the cost and use effect; the thickness of the barrier layer must be above 1μm to achieve the required barrier properties; the barrier layer uses PVA, and its water vapor barrier performance is average, which affects the service life of the present invention. Invention patent CN202211316241.8 discloses a high-barrier heavy-duty packaging one-way breathable bag. A one-way breathable valve is arranged on the front of the bag body. The film composite structure of the bag body comprises a BOPET film layer, an EVA layer, a PE modified layer coated with a filter membrane on the surface, an EMA layer and a LDPE layer in sequence. It has excellent softness and air tightness, low oxygen permeability, and improves the interlayer peeling force between the barrier functional layer and the heat sealing layer and the printed substrate layer. However, the adhesion between the heat sealing layer, the barrier layer and the base layer is not good, and EMA layers and EVA layers need to be added between the layers to improve the bonding strength between the layers, which increases the cost and process flow; the surface of the barrier layer is aluminum-plated, which reduces the folding resistance and transparency of the bag body. At the same time, the thickness of the barrier layer needs to reach more than 10μm to achieve the required barrier properties, which complicates the processing and increases the overall cost of the bag body. Summary of the invention

[0007] The main purpose of the present invention is to provide a high-barrier and high-aroma-retaining coated composite film, which has a simple structure, an easy-to-operate preparation process, a low processing cost, high oxygen barrier properties, water vapor barrier properties and aroma-retaining properties, and excellent mechanical strength, toughness and elasticity, and is not easy to break or perforate; the thickness of the isolation layer of the coated composite film is about 0.5μm, which can still ensure that the barrier layer has high oxygen barrier properties and aroma-retaining properties, thereby reducing costs and ensuring the quality and life of the product.

[0008] In order to achieve the purpose of the present invention, the present invention provides a high-barrier and high-fragrance coating composite film, comprising a substrate layer, a barrier layer, an ink layer and a heat-sealing layer arranged in sequence from the outside to the inside, the substrate layer is a NY film or a BOPP film, the barrier layer is a polyvinyl alcohol composite film, and the heat-sealing layer is a PE composite film.

[0009] NY film or BOPP film as the substrate layer has excellent transparency, mechanical properties, and has relatively good heat resistance, cold resistance, anti-slip and anti-fall properties, and is suitable for packaging products that require high-temperature processing and low-temperature storage; BOPP film as the substrate layer has better moisture and water resistance, can protect the PVA composite film, so that the present invention has better barrier stability and extends the service life of the present invention.

[0010] The polyvinyl alcohol composite film is composed of the following raw materials in parts by mass: 40-60 parts of polyvinyl alcohol, 10-15 parts of FDCA modified polyurethane compound, 8-15 parts of plasticizer, 2-4 parts of heat stabilizer, 0.1-0.3 parts of defoamer and 70-90 parts of deionized water.

[0011] The barrier layer of the present invention uses polyvinyl alcohol and FDCA modified polyurethane composite as the matrix, and cooperates with other additives (plasticizers, heat stabilizers, etc.) to produce a PVA composite film, which has better gas barrier properties, fragrance retention and structural stability, enhances the bonding force between the substrate layer and the ink layer, and improves the interlayer peeling force between the barrier layer and the substrate layer and the ink layer. At the same time, it also has a certain waterproof property, making it difficult to absorb water, ensuring the use quality and life of the present invention. The addition of FDCA modified polyurethane composite can make the thickness of the PVA composite film about 0.5μm, and its oxygen permeability can reach <1cm 3 / m 2 *d, has better gas barrier properties and reduces costs.

[0012] Furthermore, the preparation method of the FDCA-modified polyurethane composite comprises the following steps:

[0013] S1. Add polyurethane prepolymer, 1,4-butanediol and tetrabutyl titanate into a reactor, then introduce nitrogen into the reactor while stirring to exhaust the air in the container, heat to 120-130° C. and react at normal pressure for 3-4 hours, cool and evacuate to 0.08-0.1 MPa for 5-10 minutes to obtain polyurethane diol;

[0014] S2. Add the above-mentioned polyurethane diol, 2,5-furandicarboxylic acid and an appropriate amount of tetrabutyl titanate into a reaction kettle, then introduce nitrogen, raise the temperature to 190-200°C, stir and react for 2-3 hours, and distill to remove water; then evacuate the reactor to 0.1-0.2KPa, raise the temperature to 220-230°C and react for 2-4 hours to obtain an FDCA-modified polyurethane composite.

[0015] Further, the mass ratio of the polyurethane prepolymer to 1,4-butanediol is 1:(0.2-0.25);

[0016] In the step S1, the amount of tetrabutyl titanate added is 0.05-0.07% of the total mass of the polyurethane prepolymer and 1,4-butanediol;

[0017] The mass ratio of the polyurethane prepolymer to 2,5-furandicarboxylic acid is 1:(0.5-0.7).

[0018] The FDCA-modified polyurethane composite of the present invention is prepared by esterification and / or polycondensation of alcoholized polyurethane and FDCA (2,5-furandicarboxylic acid). The use of FDCA not only improves the gas barrier property of polyurethane, but also improves the water resistance and adhesion of the composite; improves the compatibility between polyurethane and polyvinyl alcohol, thereby improving the tensile strength and impact toughness of the PVA composite film, making the PVA composite film have better mechanical strength and impact resistance, and further improves the gas barrier property, fragrance retention and waterproofness of the PVA composite film, thereby extending the service life of the PVA composite film.

[0019] Furthermore, the polyurethane prepolymer is the polyurethane prepolymer LF1600D produced by Chemtura of the United States or a polyurethane prepolymer prepared by itself from TDI and polyester diol under the action of a catalyst.

[0020] Different types of polyurethane prepolymers have different modification effects, and the LF1600D of the present invention is modified by FDCA, which can ensure that the modified polyurethane composite has better gas barrier properties and can ensure the compatibility between the polyurethane composite and polyvinyl alcohol, thereby improving the comprehensive performance of the PVA composite film. If a homemade polyurethane prepolymer is used, the stability of the comprehensive performance of the PVA composite film can be guaranteed.

[0021] Further, the plasticizer is tri-n-butyl acetyl citrate or dibutyl phthalate;

[0022] The heat stabilizer is lauric acid ester or zinc stearate;

[0023] The defoamer is an organosilicon defoamer.

[0024] Using tri-n-butyl acetyl citrate or dibutyl phthalate as a plasticizer not only improves the processability, toughness and adhesion of the PVA composite film, but also improves the tensile strength and gas barrier properties of the PVA composite film.

[0025] Furthermore, the PE composite film is composed of the following raw materials in parts by mass: 100 parts of polyethylene compound, 10-20 parts of polytrimethylene carbonate, 8-12 parts of maleic anhydride grafted polyethylene, 15-30 parts of polyurethane modified epoxy resin and 1-3 parts of aromatic diamine.

[0026] The PE composite film made of polyethylene compound, polytrimethylene carbonate PTMC, and polyurethane modified epoxy resin has excellent high and low temperature resistance, heat sealing and water resistance, which can prevent the PVA composite film from being invaded by water vapor in the coated composite film, so that the present invention has high oxygen barrier and high fragrance preservation; it also has excellent adhesion or printability, and can make it possible to add no adhesive between the heat sealing layer and the ink layer, reducing costs and processing procedures. The addition of PTMC improves the puncture resistance and gas barrier properties of the PE composite film, ensuring that the PE composite film still has excellent water resistance and mechanical strength; the addition of polyurethane modified epoxy resin improves the mechanical strength, toughness and high temperature resistance of the PE composite film, and makes the PE composite film have better adhesion, while improving the gas barrier and waterproof properties of the PE composite film.

[0027] Furthermore, the polyethylene composite is a mixture of low-density polyethylene, linear low-density polyethylene and metallocene polyethylene in a mass ratio of 5:1:2.

[0028] The present invention adopts a mixture of low-density polyethylene, linear low-density polyethylene and metallocene polyethylene in a mass ratio of 5:1:2 as the matrix of the heat-sealing layer. The three cooperate with each other to make the heat-sealing layer have better heat-sealing properties, mechanical strength, water resistance and grease resistance, and improve the high and low temperature resistance, gas barrier and puncture resistance of the heat-sealing layer, thereby significantly extending the service life of the present invention.

[0029] Furthermore, the ink layer is water-based polyurethane ink, and the diluents are water and ethanol.

[0030] Furthermore, the thickness of the substrate layer is 2-10 μm, and the thickness of the heat-sealing layer is 5-20 μm. It is worth noting that the thickness of the functional layers such as the substrate layer and the heat-sealing layer can be designed according to different packaging materials. The layer thickness designed in the present invention only indicates that the film layer within this thickness range can also achieve the required performance requirements.

[0031] The present invention also provides a preparation process of a high-barrier and high-fragrance-retaining coated composite film, which specifically comprises the following steps:

[0032] P1. The prepared substrate layer is subjected to corona treatment, and then a polyvinyl alcohol emulsion is coated on the corona surface of the substrate layer, and the polyvinyl alcohol composite film is obtained by heat preservation at 130-140°C for 2h; the raw material of the polyvinyl alcohol emulsion is the raw material of the polyvinyl alcohol composite film;

[0033] P2. Printing an ink layer on one side of the polyvinyl alcohol composite film away from the substrate layer, drying after printing, and cooling to room temperature;

[0034] The raw materials of P3.PE composite film are added to the casting machine, heated to 130-140℃ to melt, and then flow out through the flat head of the casting machine. It is pressed between two closely contacting rollers to the composite layer composed of the substrate layer, the polyvinyl alcohol composite film and the ink layer to obtain a heat-sealing layer tightly attached to the ink layer. It is pressed at 60-80℃ for 0.5-1h and cooled to room temperature to obtain a high-barrier and high-flavor-retention coated composite film.

[0035] Furthermore, the coating amount of the polyvinyl alcohol composite film is 0.5-1g / m 2 , with a thickness of 0.3-0.6 μm. When the thickness of the polyvinyl alcohol composite film is 0.3-0.6 μm, its oxygen permeability is less than 1 cm 3 / m 2 *d.

[0036] The present invention has achieved the following beneficial effects:

[0037] 1. The present invention uses a coating process to coat a layer of polyvinyl alcohol composite material on the surface of the NY film or BOPP film as the substrate layer. The polyvinyl alcohol composite film after film formation has high oxygen barrier properties and fragrance retention properties; the coating process is simple, and the obtained polyvinyl alcohol composite film has excellent oxygen barrier properties when it is only about 0.5μm. The barrier layer of the present invention has better gas barrier properties and fragrance retention properties by designing suitable materials and adjusting suitable raw material ratios. At the same time, it also improves the water resistance of the PVA composite film and the bonding force with the adjacent film layer, resulting in lower processing costs of the present invention, and improves the product quality of the present invention, extending the service life and application range of the product, and can be applied to packaging materials such as food with relatively high fat content and cold fresh food.

[0038] 2. The present invention designs the formula of the PE composite material and the ratio of raw materials, and adopts the PE composite film prepared by the casting process as the heat sealing layer, which not only has excellent heat sealing performance and water resistance, but also improves the gas barrier property, printability, high temperature resistance and toughness of the heat sealing layer, ensures that the heat sealing layer is not easily punctured, and further extends the service life of the present invention.

[0039] 3. The coated composite film of the present invention is composed of a substrate layer, a barrier layer, an ink layer and a heat-sealing layer. The raw materials are environmentally friendly and easily available, the processing technology is simple, the film layers have good bonding properties and are not easy to peel off, and the film layers interact with each other, thereby ensuring that the present invention has high barrier and high fragrance retention properties, high high and low temperature resistance, high wear resistance and corrosion resistance, extending the service life of the coated composite film and broadening the application field of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 It is a schematic structural diagram of the high-barrier and high-fragrance-retaining coated composite film of the present invention.

[0041] Figure symbols: 1. substrate layer; 2. barrier layer; 3. ink layer; 4. heat sealing layer. DETAILED DESCRIPTION

[0042] The following is a clear and complete description of the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0043] like Figure 1 As shown, the present invention provides a preparation process of a high-barrier and high-fragrance coating composite film, which specifically comprises the following steps:

[0044] P1. The prepared substrate layer 1 is subjected to corona treatment, cleaning, and antistatic treatment, and then polyvinyl alcohol emulsion is coated on the corona surface of the treated substrate layer 1, and the film is kept at 130-140°C for 2 hours to obtain a polyvinyl alcohol composite film, i.e., a barrier layer 2. The voltage treatment process is: voltage 2-4kV, corona speed 40-50m / min, and treatment time 5-10s.

[0045] Preferably, the substrate layer 1 is a NY film or a BOPP film (in the embodiment of the present invention, a BOPP made by a casting process using a PP model of Borealis RD208CF is selected);

[0046] Preferably, the thickness of the substrate layer 1 is 2-10 μm;

[0047] Preferably, the coating amount of the polyvinyl alcohol composite film is 0.5-1 g / m 2, thickness is 0.3-0.6μm.

[0048] The polyethylene emulsion (i.e. the raw material of the polyvinyl alcohol composite film) is composed of the following raw materials in parts by weight: 40-60 parts of polyvinyl alcohol, 10-15 parts of FDCA modified polyurethane compound, 8-15 parts of plasticizer, 2-4 parts of heat stabilizer, 0.1-0.3 parts of defoamer and 70-90 parts of deionized water.

[0049] Preferably, the polyvinyl alcohol in the embodiment of the present invention is selected from Japan Kuraray, model CP-1000.

[0050] Preferably, the preparation method of the FDCA-modified polyurethane composite comprises the following steps, measured by weight:

[0051] S1. Add 100 parts of polyurethane prepolymer, 20-25 parts of 1,4-butanediol and 0.07-0.09 parts of tetrabutyl titanate into a reactor, then introduce nitrogen into the reactor while stirring to expel the air in the container, heat to 120-130°C and react at normal pressure for 3-4 hours, cool and evacuate to 0.08-0.1MPa and maintain for 5-10 minutes to obtain polyurethane diol.

[0052] Preferably, the polyurethane prepolymer is polyurethane prepolymer LF1600D produced by Chemtura of the United States or a polyurethane prepolymer prepared by itself from TDI and polyester diol under the action of a catalyst.

[0053] The preparation method of the homemade polyurethane prepolymer is as follows: 1 kg of polybutylene adipate (all selected from XCP-1000H of Tangyi Chemical in the embodiment of the present invention) and 400 g of diisononyl phthalate (all selected from ExxonMobil DINP in the embodiment of the present invention) are poured into a reaction kettle, the temperature is raised to 120°C, and vacuum is drawn at a rate of 1200 rpm for 2 hours while stirring, then the temperature is lowered to 60°C, the vacuum is released and nitrogen is introduced into the container, and then 350 g of toluene diisocyanate (all selected from TDI-80 of Wanhua in the embodiment of the present invention) and 1.5 g of dibutyltin diacetate are added, and then the temperature is gradually raised to 70°C and kept constant for 4 hours to obtain a homemade polyurethane prepolymer.

[0054] S2. The above-mentioned polyurethane diol, 50-70 parts of 2,5-furandicarboxylic acid (all selected from Coward Chemical in the embodiment of the present invention) and 0.01-0.02 parts of tetrabutyl titanate are added to a reaction kettle, and then nitrogen is introduced, the temperature is raised to 190-200°C, stirred for reaction for 2-3 hours, and water is distilled off; then the reaction kettle is evacuated to 0.1-0.2KPa, the temperature is raised to 220-230°C, and the reaction is carried out for 2-4 hours to obtain an FDCA-modified polyurethane composite.

[0055] Preferably, the plasticizer is tri-n-butyl acetyl citrate ATBC (selected from Vantelus ATBC of the United States in the embodiments of the present invention) or dibutyl phthalate DBP (selected from Feihong New Materials in the embodiments of the present invention).

[0056] Preferably, the heat stabilizer is lauric acid ester or zinc stearate;

[0057] Preferably, the defoamer is a silicone defoamer.

[0058] P2. Print water-based polyurethane ink (wherein the diluents are water and ethanol) on the side of the polyvinyl alcohol composite film away from the substrate layer 1, dry it after printing, and cool it to room temperature to obtain the ink layer 3. Preferably, the water-based polyurethane ink is selected from Lamberti, model PU850.

[0059] The raw material of the P3.PE composite film is added to the casting machine, heated to 130-140°C to melt, and then flows out through the flat die head, and is pressed between two closely contacting rollers to the composite layer composed of the substrate layer 1, the polyvinyl alcohol composite film and the ink layer 3 to obtain a heat-sealing layer 4 that is closely attached to the ink layer 3, and is pressed at 60-80°C for 0.5-1h, and cooled to room temperature to obtain a high-barrier and high-flavor-retaining coated composite film. Preferably, the thickness of the heat-sealing layer 4 is 5-20 μm.

[0060] The PE composite film is composed of the following raw materials in parts by mass: 100 parts of polyethylene compound, 10-20 parts of polytrimethylene carbonate, 8-12 parts of maleic anhydride grafted polyethylene, 15-30 parts of polyurethane modified epoxy resin and 1-3 parts of aromatic diamine.

[0061] Preferably, the polyethylene composite is a mixture of low-density polyethylene (selected from Shanghai Petrochemical LDPE, model N220 in the embodiments of the present invention), linear low-density polyethylene (selected from Saudi Exxon LL6201RQ in the embodiments of the present invention) and metallocene polyethylene (selected from DowDuPont 5410G in the embodiments of the present invention) in a mass ratio of 5:1:2.

[0062] Preferably, the polytrimethylene carbonate PTMC in the embodiment of the present invention is selected from Wuhan Smec Biotechnology.

[0063] Preferably, the maleic anhydride grafted polyethylene in the embodiment of the present invention is selected from Huaxiang Kejie, model ZJ-800E.

[0064] Preferably, the polyurethane modified epoxy resin in the embodiment of the present invention is selected from Dow Chemical of the United States, and the model is DER 791.

[0065] Preferably, the aromatic diamine in the embodiment of the present invention is dimethylthiotoluenediamine (DETDA), which is selected from Zhonghe Chemical and has a model number of E300.

[0066] The steps of preparing the high barrier and high aroma preservation coated composite film into packaging film are as follows: the high barrier and high aroma preservation coated composite film prepared above is cut and formed according to the set size, then bagged by heat sealing process, and then laser tearable edges are engraved to obtain the packaging film of the desired product. The heat sealing process conditions are as follows: the heat sealing temperature is 110-150℃, the pressure is 3-6kg / cm 2 .

[0067] The high barrier and high fragrance-retaining coated composite film of the present invention will be described below with reference to specific embodiments.

[0068] Example 1 Polyvinyl alcohol composite film

[0069] The polyvinyl alcohol composite film of this embodiment is prepared by coating a polyethylene emulsion on a substrate layer 1. The polyethylene emulsion is composed of the following raw materials in parts by weight: 40 parts of polyvinyl alcohol, 15 parts of FDCA-modified polyurethane compound, 10 parts of DBP, 3.2 parts of zinc stearate, 0.1 parts of silicone defoamer and 70 parts of deionized water.

[0070] The organosilicon defoamer in the embodiment of the present invention is selected from AFR-3168 of Dow Corning of the United States.

[0071] The preparation method of the FDCA-modified polyurethane composite comprises the following steps, measured by mass:

[0072] S1. Add 100 parts of polyurethane prepolymer LF1600D, 20 parts of 1,4-butanediol and 0.07 parts of tetrabutyl titanate into a reactor, then introduce nitrogen into the reactor while stirring to expel the air in the container, heat to 120°C and react at normal pressure for 4 hours, cool and evacuate to 1.0 MPa for 8 minutes to obtain polyurethane diol.

[0073] S2. The above-mentioned polyurethane diol, 50 parts of 2,5-furandicarboxylic acid and 0.01 parts of tetrabutyl titanate are added to a reactor, and then nitrogen is introduced, the temperature is raised to 190°C, stirred for reaction for 3 hours, and water is distilled off; then the reactor is evacuated to 0.1 KPa, the temperature is raised to 230°C, and the reaction is carried out for 4 hours to obtain an FDCA-modified polyurethane composite.

[0074] Example 2 Polyvinyl alcohol composite film

[0075] The polyvinyl alcohol composite film of this embodiment is prepared by coating a polyethylene emulsion on a substrate layer 1. The polyethylene emulsion is composed of the following raw materials in parts by weight: 60 parts of polyvinyl alcohol, 10 parts of FDCA-modified polyurethane compound, 15 parts of ATBC, 4 parts of zinc stearate, 0.3 parts of silicone defoamer (AFR-3168) and 90 parts of deionized water.

[0076] The preparation method of the FDCA-modified polyurethane composite comprises the following steps, measured by mass:

[0077] S1. Add 100 parts of polyurethane prepolymer LF1600D, 25 parts of 1,4-butanediol and 0.09 parts of tetrabutyl titanate into a reactor, then introduce nitrogen into the reactor while stirring to expel the air in the container, heat to 130°C and react at normal pressure for 3 hours, cool and evacuate to 0.09 MPa for 10 minutes to obtain polyurethane diol.

[0078] S2. The above-mentioned polyurethane diol, 70 parts of 2,5-furandicarboxylic acid and 0.02 parts of tetrabutyl titanate are added to a reactor, and then nitrogen is introduced, the temperature is raised to 200°C, stirred for reaction for 2 hours, and water is distilled off; then the reactor is evacuated to 0.2KPa, the temperature is raised to 230°C and the reaction is carried out for 4 hours to obtain an FDCA-modified polyurethane composite.

[0079] Example 3 Polyvinyl alcohol composite film

[0080] The polyvinyl alcohol composite film of this embodiment is prepared by coating a polyethylene emulsion on a substrate layer 1. The polyethylene emulsion is composed of the following raw materials in parts by weight: 50 parts of polyvinyl alcohol, 12 parts of FDCA-modified polyurethane compound, 10 parts of ATBC, 2.6 parts of zinc stearate, 0.2 parts of silicone defoamer (AFR-3168) and 80 parts of deionized water.

[0081] The preparation method of the FDCA-modified polyurethane composite comprises the following steps, measured by mass:

[0082] S1. Add 100 parts of polyurethane prepolymer LF1600D, 21 parts of 1,4-butanediol and 0.08 parts of tetrabutyl titanate into a reactor, then introduce nitrogen into the reactor while stirring to expel the air in the container, heat to 130°C and react at normal pressure for 4 hours, cool and evacuate to 0.09 MPa for 10 minutes to obtain polyurethane diol.

[0083] S2. The above-mentioned polyurethane diol, 65.5 parts of 2,5-furandicarboxylic acid and 0.01 parts of tetrabutyl titanate are added to a reactor, and then nitrogen is introduced, the temperature is raised to 200°C, the reaction is stirred for 3 hours, and water is distilled off; then the reactor is evacuated to 0.2 KPa, the temperature is raised to 230°C, and the reaction is carried out for 4 hours to obtain an FDCA-modified polyurethane composite.

[0084] Example 4 Polyvinyl alcohol composite film

[0085] The raw materials, preparation process, etc. of the polyethylene composite film of this embodiment are the same as those of Example 3. The difference is that the raw materials of the polyethylene emulsion in Example 4 have different mass parts, namely: 52 parts of polyvinyl alcohol, 14 parts of FDCA modified polyurethane composite, 12 parts of ATBC, 3.5 parts of zinc stearate, 0.3 parts of silicone defoaming agent (AFR-3168) and 80 parts of deionized water.

[0086] Example 5 Polyvinyl alcohol composite film

[0087] The raw materials, preparation process, etc. of the polyethylene composite film of this embodiment are the same as those of Example 4. The difference is that the polyurethane prepolymer in this embodiment 5 is homemade, and the specific preparation process has been described above.

[0088] Comparative Example 1

[0089] The raw materials, preparation process, etc. of the polyvinyl alcohol composite film in Comparative Example 1 are the same as those in Example 4, except that no FDCA-modified polyurethane composite is added in Comparative Example 1, and the amount of polyvinyl alcohol added is 66 parts.

[0090] Comparative Example 2

[0091] The raw materials, preparation process, etc. of the polyvinyl alcohol composite film in this comparative example 2 are the same as those in Example 4, except that no FDCA-modified polyurethane composite is added in this comparative example 2, and 14 parts of a mixture of polyurethane prepolymer and FDCA in a mass ratio of 1.5:1 are added.

[0092] Comparative Example 3

[0093] The raw materials, preparation process, etc. of the polyvinyl alcohol composite film in Comparative Example 3 are the same as those in Example 4, except that the polyurethane prepolymer in Comparative Example 3 is selected from the polyurethane prepolymer LF 950A of Chemtura, USA.

[0094] Comparative Example 4

[0095] The raw materials, preparation process, etc. of the polyvinyl alcohol composite film in Comparative Example 4 are the same as those in Example 4, except that 2,5-furandicarboxylic acid in Comparative Example 4 is replaced by phthalic acid, and other components and proportions remain unchanged.

[0096] Example 6 PE composite film

[0097] The PE composite film of Example 6 is composed of the following raw materials in parts by mass: 100 parts of polyethylene compound, 15 parts of polytrimethylene carbonate, 10 parts of maleic anhydride grafted polyethylene, 22 parts of polyurethane modified epoxy resin and 2 parts of aromatic diamine. The polyethylene compound is a mixture of low-density polyethylene, linear low-density polyethylene and metallocene polyethylene in a mass ratio of 5:1:2.

[0098] Comparative Example 5

[0099] The raw materials and proportions of the PE composite film in Comparative Example 5 are the same as those in Example 6, except that polytrimethylene carbonate is not added in Comparative Example 5, and the amount of the polyethylene composite added is 115 parts.

[0100] Comparative Example 6

[0101] The raw materials and proportions of the PE composite film in Comparative Example 6 are the same as those in Example 6, except that no polyurethane-modified epoxy resin is added in Comparative Example 6, and the amount of the polyethylene composite added is 122 parts.

[0102] Comparative Example 7

[0103] The raw materials and proportions of the PE composite film in Comparative Example 7 are the same as those in Example 6, except that the polyethylene composite in Comparative Example 7 is composed of low-density polyethylene and linear low-density polyethylene in a mass ratio of 5:3.

[0104] Application Example 1

[0105] The substrate layer 1, the barrier layer 2, the ink layer 3 and the heat-sealing layer 4 are sequentially arranged from the outside to the inside to form a high-barrier and high-flavor-retaining coating composite film, and the specific preparation process is as follows:

[0106] P1. The prepared BOPP substrate layer 1 was subjected to corona treatment, with a corona voltage of 4 kV, a corona speed of 40 m / min, and a treatment time of 8 s, and then cleaned and destaticized. Then, the BOPP corona surface was coated with the polyvinyl alcohol emulsion prepared in Example 1, and kept at 140° C. for 2 h to obtain a polyvinyl alcohol composite film, i.e., barrier layer 2. The thickness of the BOPP substrate layer 1 was about 7 μm; the thickness of the barrier layer 2 was about 0.6 μm.

[0107] P2. Print water-based polyurethane ink on the side of the polyvinyl alcohol composite film away from the substrate layer 1, dry it after printing, and cool it to room temperature to obtain the ink layer 3. The thickness of the ink layer 3 is about 1.0 μm.

[0108] P3. Add the raw material of the PE composite film in Example 6 into a casting machine, heat it to 140°C to melt, then flow out through a flat die head, press it between two closely contacting rollers to a composite layer consisting of a substrate layer 1, a polyvinyl alcohol composite film and an ink layer 3, obtain a heat-sealing layer 4 that is closely attached to the ink layer 3, press it at 70°C for 45 minutes, cool it to room temperature, and obtain a high-barrier and high-flavor-retaining coated composite film. The thickness of the heat-sealing layer 4 is 10 μm.

[0109] It is worth noting that in the application process of the present invention, the coating amount of the polyvinyl alcohol emulsion is controlled at 0.5-1g / m 2, the barrier layer 2 of the required thickness can be obtained. The specific coating amount depends on the actual situation, and the coating uniformity deviation is less than 0.2g / m 2 .

[0110] Application Example 2

[0111] The structure and preparation process of the high-barrier and high-fragrance coating composite film in Application Example 2 are the same as those in Application Example 1. Please refer to Application Example 1 for details. The difference is that the polyvinyl alcohol emulsion is prepared according to Example 2.

[0112] Application Example 3

[0113] The high-barrier and high-fragrance coating composite film is different from Application Example 1 in that the polyvinyl alcohol emulsion is prepared according to Example 3.

[0114] Application Example 4

[0115] The high-barrier and high-fragrance coating composite film is different from Application Example 1 in that the polyvinyl alcohol emulsion is prepared according to Example 4, and the thickness of the barrier layer 2 is about 0.5 μm.

[0116] Application Example 5

[0117] The high-barrier and high-fragrance coating composite film is different from Application Example 1 in that the polyvinyl alcohol emulsion is prepared according to Example 5, and the thickness of the barrier layer 2 is about 0.5 μm.

[0118] Application Comparative Example 1

[0119] The structure and preparation process of the high-barrier and high-fragrance coating composite film in the comparative example 1 of this application are the same as those in the application example 4. Please refer to the application example 4 for details. The difference is that the polyvinyl alcohol emulsion is prepared according to the comparative example 1.

[0120] Application Comparative Example 2

[0121] The high-barrier and high-fragrance coating composite film is different from Application Example 4 in that the polyvinyl alcohol emulsion is prepared according to Comparative Example 2.

[0122] Application Comparative Example 3

[0123] The high-barrier and high-fragrance-retaining coated composite film is different from Application Example 4 in that the polyvinyl alcohol emulsion is prepared according to Comparative Example 3.

[0124] Application Comparative Example 4

[0125] The high-barrier and high-fragrance coating composite film is different from Application Example 4 in that the polyvinyl alcohol emulsion is prepared according to Comparative Example 4.

[0126] Application Comparative Example 5

[0127] The high-barrier and high-fragrance-retaining coated composite film is different from Application Example 4 in that the PE composite film is prepared according to Comparative Example 5.

[0128] Application Comparative Example 6

[0129] The high-barrier and high-fragrance-retaining coated composite film is different from Application Example 4 in that the PE composite film is prepared according to Comparative Example 6.

[0130] Application Comparative Example 7

[0131] The high-barrier and high-fragrance-retaining coated composite film is different from Application Example 4 in that the PE composite film is prepared according to Comparative Example 7.

[0132] The high-barrier and high-fragrance-retaining coated composite film samples prepared in Application Examples 1-5 and Comparative Examples 1-7 were tested for gas permeability, water vapor permeability, adhesion, puncture resistance, etc. The test results are shown in Table 1 below.

[0133] The detection method is as follows:

[0134] Oxygen permeability: tested according to GB / T 1038-2022 Test method for gas permeability of plastic films and sheets;

[0135] Water vapor transmission rate (37°C, 90% humidity): Tested according to GB / T 1037-2021 Test method for water vapor transmission of plastic film and sheet;

[0136] Interlayer peeling strength (peeling strength between the heat sealing layer and the composite layer consisting of the substrate layer, the polyvinyl alcohol composite film and the ink layer): tested according to the standard of GB / T 8808-88 Peeling test method for soft composite plastic materials;

[0137] Puncture resistance: according to the provisions of "6.6.13 Puncture strength" in GB / T 10004-2008. Use a 1mm puncture needle to pierce the heat seal layer from one side, read the maximum load of the needle penetrating the aluminum-plastic film, and then pull out the puncture needle after piercing the heat seal layer, heat the heat seal layer, and observe whether there are holes on the heat seal layer.

[0138] Table 1 Performance test results of high barrier and high fragrance protection coated composite films

[0139]

[0140]

[0141] It can be seen from the test results in Table 1 above that the high-barrier and high-flavor-retaining coated composite film of the present invention has lower oxygen and water vapor throughput, and the heat-sealing layer 4 has better adhesion and puncture resistance.

[0142] The technical features of the above embodiments may be combined arbitrarily. To make the description concise, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0143] The above embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the present invention. It should be pointed out that, for those of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention.

Claims

1. A high-barrier and high-flavor-retaining coated composite film, comprising a substrate layer (1), a barrier layer (2), an ink layer (3) and a heat-sealing layer (4) arranged in sequence from the outside to the inside, characterized in that: The substrate layer (1) is a NY film or a BOPP film, the barrier layer (2) is a polyvinyl alcohol composite film, and the heat sealing layer (4) is a PE composite film; The polyvinyl alcohol composite film is composed of the following raw materials in parts by weight: 40-60 parts of polyvinyl alcohol, 10-15 parts of FDCA modified polyurethane compound, 8-15 parts of plasticizer, 2-4 parts of heat stabilizer, 0.1-0.3 parts of defoamer and 70-90 parts of deionized water; The preparation method of the FDCA-modified polyurethane composite comprises the following steps: S1. Add polyurethane prepolymer, 1,4-butanediol and tetrabutyl titanate into a reactor, then introduce nitrogen into the reactor while stirring to exhaust the air in the container, heat to 120-130° C. and react at normal pressure for 3-4 hours, cool and evacuate to 0.08-0.1 MPa for 5-10 minutes to obtain polyurethane diol; S2. The polyurethane diol, 2,5-furandicarboxylic acid and an appropriate amount of tetrabutyl titanate are added to a reaction kettle, and then nitrogen is introduced, the temperature is raised to 190-200° C., the reaction is stirred for 2-3 hours, and water is distilled off; the reaction kettle is then evacuated to 0.1-0.2 KPa, the temperature is raised to 220-230° C., and the reaction is carried out for 2-4 hours to obtain an FDCA-modified polyurethane composite; The polyurethane prepolymer is the polyurethane prepolymer LF1600D of Chemtura of the United States or a polyurethane prepolymer prepared by TDI and polyester diol under the action of a catalyst; The PE composite film is composed of the following raw materials in parts by mass: 100 parts of polyethylene compound, 10-20 parts of polytrimethylene carbonate, 8-12 parts of maleic anhydride grafted polyethylene, 15-30 parts of polyurethane modified epoxy resin and 1-3 parts of aromatic diamine.

2. The high barrier and high fragrance-retaining coated composite film according to claim 1, characterized in that: The mass ratio of the polyurethane prepolymer to 1,4-butanediol is 1:(0.2-0.25); In the step S1, the amount of tetrabutyl titanate added is 0.05-0.07% of the total mass of the polyurethane prepolymer and 1,4-butanediol; The mass ratio of the polyurethane prepolymer to 2,5-furandicarboxylic acid is 1:(0.5-0.7).

3. The high-barrier and high-fragrance coating composite film according to claim 1, characterized in that: The plasticizer is tri-n-butyl acetyl citrate or dibutyl phthalate; The heat stabilizer is lauric acid ester or zinc stearate; The defoamer is an organosilicon defoamer.

4. The high-barrier and high-fragrance coating composite film according to claim 1, characterized in that: The polyethylene compound is prepared by mixing low-density polyethylene, linear low-density polyethylene and metallocene polyethylene in a mass ratio of 5:1:

2.

5. The high-barrier and high-fragrance coating composite film according to claim 1, characterized in that: The ink layer (3) is water-based polyurethane ink, and the diluents are water and ethanol.

6. The high-barrier and high-fragrance coating composite film according to claim 1, characterized in that: The thickness of the substrate layer (1) is 10-2 μm; The thickness of the heat-sealing layer (4) is 5-20 μm.

7. A process for preparing a high-barrier and high-fragrance coating composite film as claimed in any one of claims 1 to 6, characterized in that: The specific steps include: P1. The prepared substrate layer (1) is subjected to corona treatment, and then a polyvinyl alcohol emulsion is coated on the corona surface of the substrate layer (1), and the polyvinyl alcohol composite film is obtained by heat preservation at 130-140° C. for 2 hours; the raw material of the polyvinyl alcohol emulsion is the raw material of the polyvinyl alcohol composite film; P2. Printing an ink layer (3) on the side of the polyvinyl alcohol composite film away from the substrate layer (1), drying after printing, and cooling to room temperature; The raw materials of the P3.PE composite film are added to a casting machine, heated to 130-140°C to melt, and then flow out through the flat head of the casting machine. They are pressed between two closely contacting rollers toward a composite layer consisting of a substrate layer (1), a polyvinyl alcohol composite film and an ink layer (3), thereby obtaining a heat-sealing layer (4) in close contact with the ink layer (3). The raw materials are pressed at 60-80°C and cooled to room temperature to obtain a high-barrier and high-flavor-retaining coated composite film.

8. The high-barrier and high-fragrance coating composite film according to claim 7, characterized in that: The coating amount of the polyvinyl alcohol composite film is 0.5-1g / m 2 , thickness is 0.3-0.6μm.

Citation Information

Patent Citations

  • A high-barrier heavy-duty packaging unidirectional breathable bag and its preparation method

    CN115648765B

  • Homogenized olefin packaging self-standing bag and preparation method thereof

    CN113997665A

  • Polyurethane, high-solid-content waterborne polyurethane emulsion and preparation method of high-solid-content waterborne polyurethane emulsion

    CN114790273A